The Question of Relapse of a Cardiac Myxoma: an Unusual Case from Practice - Vitovskiy, R. M.; IsaіenkoV. V.; Pishchurin, O. A.; Jakovenko, I. G.; Onishchenko, V. F. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Various studies demonstrate that recurrence of cardiac myxoma (CM) occurs in 2.1–5.3% of cases. In cases of treatment of familial myxoma, the need for reoperations can reach 20–25%. It should be taken into account that among all benign cardiac tumors, CM is detected in up to 80% of cases, and the need for its surgical removal is beyond doubt. The aim. To present a case that is of particular interest due to an unusual multiple myxomas lesion of the heart of multi-chamber localization. Material and methods. This article presents an unusual case of detecting multiple myxomas of multi-cameral heart lesions 6 years after removal of myxoma of the left atrium of typical localization. The distinguishing feature of the course of the disease lies in the fact that in this case, a careful study of the life history did not reveal the characteristic signs of familial myxomas and Carney complex which is most often characteristic of multi-chamber lesions of the heart by a tumor process. At the same time, during the surgical removal of the myxoma of the left ventricle, the myxomas of the left and right atrium were revealed, which began to grow. A technical feature of the removal of the left ventricular myxoma of the apical localization was the use of video cameras and instruments for thoracoscopic surgery, which greatly facilitated revi-sion and removal of the hard-to-reach neoplasm. Our experience in surgical treatment of CM equals to 868 operations. Wherein, repeated operations performed in 12 patients were due to recurrence or appearance of a tumor in place other than the primary localization. Conclusions. CM recurrence is one of infrequent complications in the postoperative period, which, however, requires some vigilance and annual Echo monitoring. In the vast majority of cases, CM was represented by the so-called sporadic myxomas, which are more often localized in the left atrium, and rarely recur. If CM is suspected, it is necessary to exclude the possibility of “myxoma syndrome”, which has the frequency of 0.8%, according to our data. The use of the instruments for thoracoscopic surgery can greatly facilitate the removal of hard-to-reach heart tumors localization.